2016
DOI: 10.1177/0266666915573551
|View full text |Cite
|
Sign up to set email alerts
|

Can micro-enterprises leverage on the adoption of corporate websites to bolster their brand visibility? Examining salient adoption issues in Nigeria

Abstract: The present study seeks to bring to the fore contextual factors that are influencing the decision-making process of corporate website adoption among micro-enterprises in the context of the developing world. We argue that the adoption of corporate websites by the decision-makers of micro-enterprises could be a strategic lever for micro-enterprises’ brands to gain visibility in the marketplace. We further opine that for micro-enterprises to gain a foothold in doing business in the present information age, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 46 publications
2
28
3
Order By: Relevance
“…However, Kamble, Gunasekaran, and Sharma [55] and Chauhan, Singh, and Luthra [28] concluded that the adoption of Industry 4.0 by a company is related to potentialities such as resistance to change, lack of standards and regulations, and privacy, which is in line with the results of the present study. Furthermore, Lin, Lee, Lau, and Yang [59] confirmed that technological incentives have a critical role in the adoption of Industry 4.0, and Lin, Lee, Lau, and Yang [59] and Osakwe et al [91] confirmed that the most significant influence driving the adoption of technologies is perceived advantage, which is inconsistent with the results of the present research. Moreover, Yadav, Luthra, Jakhar, Mangla, and Rai [56] confirmed that the high cost of implementation and lack of resources are significant economic challenges, and poor management and policy conflict are the most significant managerial challenges.…”
Section: Discussioncontrasting
confidence: 99%
“…However, Kamble, Gunasekaran, and Sharma [55] and Chauhan, Singh, and Luthra [28] concluded that the adoption of Industry 4.0 by a company is related to potentialities such as resistance to change, lack of standards and regulations, and privacy, which is in line with the results of the present study. Furthermore, Lin, Lee, Lau, and Yang [59] confirmed that technological incentives have a critical role in the adoption of Industry 4.0, and Lin, Lee, Lau, and Yang [59] and Osakwe et al [91] confirmed that the most significant influence driving the adoption of technologies is perceived advantage, which is inconsistent with the results of the present research. Moreover, Yadav, Luthra, Jakhar, Mangla, and Rai [56] confirmed that the high cost of implementation and lack of resources are significant economic challenges, and poor management and policy conflict are the most significant managerial challenges.…”
Section: Discussioncontrasting
confidence: 99%
“…The key informants in the study were business owners, CEOs/MDs, and managers of these fi rms. For the purpose of clarity, we defi ned small-sized agribusiness fi rm in line with the World Bank's classifi cation of micro, small and medium-sized enterprises (see Osakwe et al, 2015b), specifi cally, a small-sized agribusiness fi rm is an agribusiness that is manned by 10 to 49 staff . About 55 percent of the fi rms had been in the agribusiness sector for at least seven years while the rest of the fi rm has spent between one to six years in the sector.…”
Section: Research Setting Sample Objects and Relevant Sourcesmentioning
confidence: 99%
“…This presence is achieved by means of the internet and the world wide web, which are great allies for the dissemination of corporate and commercial information, allowing SMEs to access global markets, interact with potential customers and improve their corporate image (Chaffey & Smith, 2013;Olvera-Lobo & Castillo-Rodríguez, 2018). As a result, it is undoubtable that a corporate website is one of the most important public relations vehicles for a company, as it enables them to foster engagement and gain the attention of users (Alcaide et al, 2013;Kotler & Armstrong, 2007;Osakwe et al, 2016;Peris-Ortiz et al, 2014).…”
mentioning
confidence: 99%